Vultures of paradise - Misra, Atulya (New Delhi Rupa, 2021)
A story of greed, love and sacrifice narrated in the backdrop of a crippling human tragedy. Acclaimed author Atulya Misra tells a gripping and powerful story that traverses numerous cultures and geographies. The story follows the life of Neha, who, at first, is driven by blind ambition. The heights she achieves in business dissipate once she starts spiralling in the opposite direction. Just when she appears to be an abysmal failure in the eyes of everyone, Neha creates a corporation to counter the biggest threat to the planet$1 (Bthe human propensity to consume endlessly and create more and more waste. Her enterprise becomes so large and successful that it becomes a danger to the very people who created it. Humanity has been a parasite for long enough on this planet. It$1 (Bs time we become vultures and clean up our habitat.s
Keywords: Fiction; IAS as an author